A PARP1-related prognostic signature constructing and PARP-1 inhibitors screening for glioma - Li, Hui; Wang, Zhenhua; Hou, Yuanyuan; Xi, Jianxin; He, Zhenqiang; Lu, Han; Du, Zhishan; Zhong, Sheng; Yang, Qunying (Frontiers in Cell and Developmental Biology, 2022)
The current standard treatments of glioma include surgical resection, supplemented with radiotherapy and chemotherapy, but the prognosis is poor. PARP-1 (Poly ADP-ribose polymerase 1) is a hot spot for cancer-targeted therapy and was reported to be significantly elevated in glioma. In this study, we analyzed the role of PARP-1 in DNA damage repair, constructed a PARP1-related DNA-repair prognostic signature (DPS), and screened targeted drugs for glioma. RNA-seq data of 416 glioma samples were downloaded from the GEO (Gene Expression Omnibus) database and divided into PARP1_H and PARP1_L according to the expression level of PARP-1. First, we systematically analyzed the influence of PARP-1 on DNA damage repair, prognosis, and chemoradiotherapy sensitization of glioma. All glioma patients and patients with radiotherapy or chemotherapy had a better prognosis in PARP1_L than in PARP1_H. Next, differentially expressed DNA-repair related genes (DEGs) were identified between PARP1_H and PARP1_L by LASSO (Least Absolute Shrinkage and Selection Operator) Cox analysis and applied for constructing DPS. Based on the four-gene DPS, we then developed a new nomogram to assess overall survival in glioma patients. Additionally, PARP-1 was proved an effective target for glioma therapy. So, a series of computer-aided techniques, including Discovery Studio 4.5, Schrodinger, and PyMol, were applied for the virtual screening of favorable PARP-1 inhibitors. In conclusion, this study investigated the effect of PARP-1 on glioma prognosis and the sensitization effect of radiotherapy and chemotherapy, established a novel nomogram to evaluate the overall survival of glioma patients, and further explored targeted therapy for glioma.